Compatibilization of polyethylene/polyamide 6 blend nanocomposite films. Issue 6 (16th March 2015) - Mistretta, M.C.; Ceraulo, M.; La Mantia, F.P.; Morreale, M.
Abstract : Polymer blends of incompatible components need to undergo compatibilization, in order to give rise to a blend with good physical properties. At the same way, polymer/clay nanocomposites show this problem because of different chemical nature of the polymer matrix and of the clay. Compatibilization is therefore more necessary if an incompatible polymer blend is filled with an organomodified clay in order to give a final material with good properties. In this work, a polyethylene/polyamide 6 blend filled with an organomodified clay has been compatibilized with a maleic anhydride grafted SEBS (styrene‐ethylene‐butylene‐styrene) copolymer and a glicidylmethacrylate‐ethylene copolymer. The results show that compatibilization improves the mechanical properties in terms of elongation at break, as well as the rheological properties under nonisothermal elongational flow; furthermore, an unexpected effect has been found, since going from the isotropic to the anisotropic material, a fragile‐ductile transition occurs, with a significant increase of the elongation values, while a small reduction of the elastic modulus was found, because of the lower crystallinity in comparison to isotropic samples. POLYM. COMPOS., 36:992–998, 2015. © 2015 Society of Plastics Engineers